MULTIMEDIA TECHNOLOGY IN TEACHING ENGLISH TO YOUNG LEARNERS - Kemala, Rd. Talitha Rahma (2016)
This study is aimed to investigate the utilization of multimedia technology in teaching English to young learners. This study also describes the students' responses and the teachers' perception toward the use of multimedia technology in English teaching and learning activities. Participants in this study were forty young learners and three in-service teachers of EFL working at a private English course. The data were collected through classroom observations, questionnaires, and interviews. The data from the instruments were analyzed qualitatively. The result indicates that the teachers utilize the multimedia technology as a tool which helps them to (1) gain students' attention, (2) recall prerequisites, (3) present learning objectives, (4) support learning through examples and visual elaboration, (5) elicit students' responses, (6) provide feedback, (7) enhance retention and transfer the abstract concept, (8) assess students' performance. The result also shows that the students give positive responses toward the use of multimedia technology to support their English acquisition and the teachers have positive perspective toward the use of multimedia technology in teaching English to young learners.